Maintenance of a central high frequency synapse in the absence of synaptic activity - Lessle, Sascha; Ebbers, Lena; Dörflinger, Yvette; Hoppe, Simone; Kaiser, Michaela; Nothwang, Hans Gerd; Körber, Christoph (Frontiers in cellular neuroscience, 2024)
Activity has long been considered essential for circuit formation and maintenance. This view has recently been challenged by proper synaptogenesis and only mildly affected synapse maintenance in the absence of synaptic activity in forebrain neurons. Here, we investigated whether synaptic activity is necessary for the development and maintenance of the calyx of Held synapse. This giant synapse located in the auditory brainstem is highly specialized to maintain high frequency, high-fidelity synaptic transmission for prolonged times and thus shows particularly high synaptic activity. We expressed the protease tetanus toxin light chain (TeNT) exclusively in bushy cells of the ventral cochlear nucleus (VCN) of juvenile mice. Since globular bushy cells give rise to the calyx of Held, expression of TeNT in these cells specifically abolished synaptic transmission at the calyx without impairing general functionality of the central auditory system. Calyces lacked synaptic activity after two weeks of TeNT expression. However, this did not lead to major changes in presynaptic morphology, the number of active zones (AZs) or the composition of postsynaptic AMPA-type glutamate receptors (GluAs). Moreover, the fenestration of the calyx of Held, a hallmark of structural maturation, occurred normally. We thus show that the maintenance of a specialized high frequency synapse in the auditory brainstem occurs in a hardwired, probably genetically encoded, manner with little dependence on synaptic activity.
Gesehen am 11.06.2025